PEDAGOGICAL AND PSYCHOLOGICAL PROBLEMS OF PREPARING STUDENTS FOR VOLUNTEER ACTIVITIES - Khushnazarova Mamura Nodirovna (American Journals, 2023)
This article talks about the development of the potential of volunteering in solving social problems of society, that it is an effective means of improving the welfare of the population, developing volunteering, actively involving the younger generation in volunteering, becoming one of the priorities of state policy in our country.
Keywords: volunteer potential, professional development, professional inclinations, professional qualities, pedagogical-psychological, professional-creative activity, organization, management, intuition.